SARANA TRANSPORTASI SEBAGAI DAYA TARIK WISATA: KAJIAN PERSEPSI WISATAWAN BERKUNJUNG KE KEPULAUAN SERIBU STUDI KASUS: KAPAL KM SABUK NUSANTARA 66 - Kadek Wiweka; Suci Sandi Wachyuni; Putu Pramania Adnyana; Anjani Nurul Safitri (Journal of Tourism and Economic, 2020)
Historically until now, accessibility, especially transportation, has played an important role in tourism development. This study aims to identify tourists erceptions of tourist transportation (KM Sabuk Nusantara 66) as an attraction for tourists visiting the Kepulauan Seribu from the port of Sunda Kelapa. This study adopted a qualitative approach to triangulation data collection techniques. The research location was carried out at Sunda Kelapa Port, involving the ship captain (PT. Pelni) and the KSOP Sunda Kelapa Port staff. The number of samples determined using a purposive sampling technique. Meanwhile, tourists are determined by the judgmental sampling technique. This data collection was carried out for three months, from May to July 2018. This study found that the KM Sabuk Nusantara 66 Ship's feasibility is following tourists' perceptions based on 10 indicators of transportation factors to support tourism. This research can be used to suggest ship operators and destination managers' development improve service quality continuously. This study has limitations on the sample of transportation companies involved. Future research is expected to reach a wider sample or even reach other transportation types, such as tourist trains, tour buses, or even air transportation.